The Method of Estimating the Premium in Mergers and Acquisitions in Emerging Markets for Private Companies - Elena V. Ryabova; Valentina V. Petrova (Финансы: теория и практика)
Introduction. In the context of globalization of economies mergers and acquisitions (in short M&A) are becoming increasingly important in business, as a strategic development of companies. M&A deals, as a rule, are assessed for their efficiency for acquiring company and/or for target-company. There are a lot of papers and empirical studies on this subject. However, most of them concern public companies with shares listed on the stock exchange.Moreover, in the last decade M&A deals were most typical for private owned companies operating in an emerging capital market. Due to the imperfections of an emerging capital market, lack of available and reliable information about private target-companies, investors need a methodology able to take into account these features of the market, to more reasonably calculate the transaction price and the premium in its structure.Topic. As the object of the study we analyse mergers and acquisitions in the countries of the BRICS group (Brazil, Russia, India, China, South Africa) for 2005–2015.Purpose. The purpose of this study is development of methodological apparatus for assessment of premiums in M&A transactions for private companies in emerging capital markets.Methods. As research methods were used general scientific methods (analysis, synthesis, comparison, graphics), and special ones (statistical analysis methods, the coefficient method).Results. In this article we present the author’s approach to the assessment of fair market value and premiums in M&A transactions with private companies in emerging capital markets. We also conducted testing of proposed methodology.Implementation. The proposed methodology can be used by both external and internal analysts to calculate and justify the premium in deals with private companies in emerging capital markets.